2008 IEEE Industry Applications Society Annual Meeting 2008
DOI: 10.1109/08ias.2008.35
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Finite Element and Analytical Models in the Optimal Multi-Domain Design of Machines : Application to an Interior Permanent Magnet Starter Generator

Abstract: This paper proposes to apply optimal multiphysic models to the design of highly constrained electrical machines, such as interior permanent magnet machine (IPM) intended for an automotive integrated starter generators (ISG). One of the main problems in the use of such optimal approaches remains the accuracy of the models used by the optimizer. In a previous paper [1], we proposed a design model linked to three strong hypotheses : 1) Iron losses are calculated according to the flux density fundamental (sinusoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The result from the experiment has proved that rotor core is extremely hotter than expected [40]. Jérome Legranger, et al, (2010) presented in the optimal multi physics design of machines of an Interior Permanent-Magnet Starter Generator with a blend of FE and analytical models. To forecast the stator winding and rotor magnet's temperature, a thermal model may be used which is a 3-D transient lumped-parameter network.…”
Section: Thermal Modelmentioning
confidence: 97%
See 2 more Smart Citations
“…The result from the experiment has proved that rotor core is extremely hotter than expected [40]. Jérome Legranger, et al, (2010) presented in the optimal multi physics design of machines of an Interior Permanent-Magnet Starter Generator with a blend of FE and analytical models. To forecast the stator winding and rotor magnet's temperature, a thermal model may be used which is a 3-D transient lumped-parameter network.…”
Section: Thermal Modelmentioning
confidence: 97%
“…The archetype has temperature sensors in various key points of the stator machine. The experimental study is based on the measure of three points (i) slot temperature (145°C); (ii) end winding temperature (146°C); (iii) tooth temperature (110°C) [61]. To avoid the excessive cooling requirements, the stator windings' current density is restricted to 3-6 A/mm 2 and the current loading to 40-60 kA/m [77].…”
Section: Thermal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess the machine performance, the researcher used a coupled field and circuit model which was solved using the time-stepping finite-element technique [127]. In 2008 [128], and 2010 [129], conducted a comparison of different configurations in an axial-flux nine-phase concentrated-winding PMSG for a direct-drive wind turbine.…”
Section: Novel Topology Development In Pmsgsmentioning
confidence: 99%
“…Besides permanent magnet poles on the rotor, tooth-harmonic coils were installed on the rotor which generates voltage induced by the inherent tooth harmonic magnetic fields as a result of slots, then after rectification, the tooth-harmonic coils supply DC field current to the excitation windings on the rotor. In all of these research efforts, hybrid excitation machines showed certain attractive performance features, but a wide speed range flux weakening performance was still difficult to achieve [6][7][8].…”
Section: Introductionmentioning
confidence: 99%